A Journey Across the UAE Culture through the Voices of Young Emirati Women: Texts in Northern Emirati Arabic (Dubai, Ajman, and Sharjah) - Kalach, Najla (Folia Orientalia, 2021)
Although some Gulf varieties, such as Emirati Arabic, varieties have been gaining more attention in recent years, further investigation and resources need to be made available to the scientific community. The aim of this article is to offer the Gulf Arabic studies a contribution by presenting a selection of texts in the spoken varieties of Dubai, Sharjah and Ajman, which were recorded between 2015 and 2017, during fieldworks in the United Arab Emirates. The speakers are young women between the age of 21 and 31 and the topics regard the Emirati heritage, in order to add cultural value to the linguistic subject. The transcribed texts can provide further bases for comparison in the Emirati Arabic studies.